2014
DOI: 10.4049/jimmunol.1302167
|View full text |Cite|
|
Sign up to set email alerts
|

Macrophage PTEN Regulates Expression and Secretion of Arginase I Modulating Innate and Adaptive Immune Responses

Abstract: The activation of innate immune cells triggers numerous intracellular signaling pathways, which require tight control to mount an adequate immune response. The PI3K signaling pathway is intricately involved in innate immunity, and its activation dampens the expression and release of proinflammatory cytokines in myeloid cells. These signaling processes are strictly regulated by the PI3K antagonist, the lipid phosphatase, PTEN, a known tumor suppressor. Importantly, PTEN is responsible for the elevated productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 40 publications
2
98
0
Order By: Relevance
“…66 In addition, CEBPB is capable of increasing the expression of central nervous system genes such as Choline O-Acetyltransferase (ChAT) that encodes an enzyme which catalyzes the biosynthesis of the neurotransmitter acetylcholine. 67 Given the small samples sizes our findings should be followed up in larger cohorts of postmortem brain samples.…”
Section: Discussionmentioning
confidence: 99%
“…66 In addition, CEBPB is capable of increasing the expression of central nervous system genes such as Choline O-Acetyltransferase (ChAT) that encodes an enzyme which catalyzes the biosynthesis of the neurotransmitter acetylcholine. 67 Given the small samples sizes our findings should be followed up in larger cohorts of postmortem brain samples.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN deletion can induce arginase I expression and secretion by increasing the expression of C/EBPβ and STAT3. 75 In addition, it can enhance GKS3β activation and thus promote an inflammatory response to TLR agonists in macrophages. 73 Kamo et al 76 found that the knockdown of PTEN could promote AKT/β-catenin/Foxol signaling and could down-regulate TLR4 expression in mouse liver cells responding to ischemia/reperfusion injury.…”
Section: Functions Of Pten In Innate Immunity and Antiviral Defensementioning
confidence: 99%
“…C57BL/6 mice were immunized at day 0 according to the protocol described recently in Sahin et al (44). Progression of EAE was divided into five clinical stages: score 0, no signs; score 1, complete tail paralysis; score 2, partial paraparesis; score 3, severe paraparesis; score 4, tetraparesis; and score 5, moribund condition.…”
mentioning
confidence: 99%